Mutagenesis and carcinogenesis induced by dibenzo[a,l]pyrene in the mouse oral cavity: a potential new model for oral cancer - Guttenplan, Joseph B. (2011)
Cancer of the oral cavity is a serious disease, affecting about 30,000 individuals in US annually. There are several animal models of oral cancer, but each has certain disadvantages. As a new model, we investigated whether topical application of the tobacco smoke carcinogen, dibenzo[a,l]pyrene (DB[a,l]P) is mutagenic and carcinogenic in the oral cavity of the B6C3F1 lacI and B6C3F1 mouse, respectively. B6C3F1 lacI mice received DB[a,l]P (0, 3, 6, 12 nmol) 3× per week. B6C3F1 mice received the same doses and also 24 nmol. At 38 weeks mutagenesis was measured in oral tissues in lacI mice. For the high dose group, the mutant fraction (MF) in upper mucosa and tongue increased about twofold relative to that in vehicle-alone. The increases were statistically significant. The mutational profile in the DB[a,l]P-induced mutants was compared with that induced by benzo[a]pyrene (BaP) in oral tissue. BaP is mutagenic in many tissues when administered by gavage. The mutational profile for DB[a,l]P was more similar to that reported for p53 mutations in head and neck cancers than was that of BaP. At 47 weeks, oral squamous cell carcinomas (OSCC) were found in 31% of the high-dose B6C3F1 group. Elevations of p53 and COX-2 protein were observed in tumor and dysplastic tissue. As DB[a,l]P induces mutations and tumors in the oral cavity, and has a mutational profile in oral tissue similar to that found in p53 in human OSCC, the treatment protocol described here may represent a new and relevant model for cancer of the oral cavity.